1996
DOI: 10.1016/s0896-6273(00)80055-0
|View full text |Cite
|
Sign up to set email alerts
|

Direct Activation of the Olfactory Cyclic Nucleotide–Gated Channel through Modification of Sulfhydryl Groups by NO Compounds

Abstract: The activation of a cyclic nucleotide-gated channel is the final step in sensory transduction in olfaction. Normally, this channel is opened by the intracellular cyclic nucleotide second messenger cAMP or cGMP. However, in single channel recordings we found that donors of nitric oxide, a putative intercellular messenger, could directly activate the native olfactory neuron channel. Its action was independent of the presence of the normal ligand and did not involve the cyclic nucleotide binding site, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
104
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 44 publications
4
104
1
Order By: Relevance
“…Schmachtenberg et al (2000Schmachtenberg et al ( , 2003 reported that NO-stimulus induces outward potassium currents in 30 out of 72 olfactory cells and inward potassium currents in 3 out of 54 cells by physiological study [36,37]. In the cilia of rat olfactory cells, moreover, NO-stimulus is reported to activate or inhibit olfactory cyclic nucleotidegated (CNG) channels [5,6,28,36,37]. These reports suggest that NO is produced by the olfactory cells in response to odorant-stimulus, and has inhibitory and/or weakly excitatory effects to the olfactory cells by gating of CNG channel.…”
mentioning
confidence: 99%
“…Schmachtenberg et al (2000Schmachtenberg et al ( , 2003 reported that NO-stimulus induces outward potassium currents in 30 out of 72 olfactory cells and inward potassium currents in 3 out of 54 cells by physiological study [36,37]. In the cilia of rat olfactory cells, moreover, NO-stimulus is reported to activate or inhibit olfactory cyclic nucleotidegated (CNG) channels [5,6,28,36,37]. These reports suggest that NO is produced by the olfactory cells in response to odorant-stimulus, and has inhibitory and/or weakly excitatory effects to the olfactory cells by gating of CNG channel.…”
mentioning
confidence: 99%
“…This may reflect a feedback mechanism, because calcium entry through NMDA receptors stimulates NO formation. The cyclic nucleotide-gated H AC channel might be normally activated by NO Snitrosylation, because HAC channels resemble olfactory cyclic nucleotide-gated channels, which are known to be activated by NO (24).…”
mentioning
confidence: 99%
“…As well as indirectly activating CNG channels by stimulating cGMP synthesis, NO directly activates CNG channels in olfactory neurons by covalently modifying the channel protein 18 . In our experiments, SNC applied directly onto excised inside-out patches from cone terminals failed to activate CNG channels and had no effect on the sensitivity of the channels to cGMP (n = 5).…”
mentioning
confidence: 99%